DEVELOPMENT OF PHYSICAL QUALITIES IN FEMALE CADETS OF THE ACADEMY OF THE MINISTRY OF INTERNAL AFFAIRS IN FUNCTIONAL ALL-AROUND (CROSSFIT) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The optimization of physical education and sports contributes to the popularization of the population, schoolchildren, youth, and the community of turmush as necessary conditions and opportunities for participation in national sports events.